Wear-resistant eutectic high-entropy alloy powder for additive manufacturing as well as preparation method and application of wear-resistant eutectic high-entropy alloy powder
By adjusting the temperature and pressure during the aerosolization powder of high-entropy alloy powder and adding W elements, the problem of insufficient hardness and furnace blocking in additive manufacturing of high-entropy alloy powder is solved, and high hardness and wear resistance are achieved effect.
Patent Information
- Application Number
- CN202411526662.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing high-entropy alloy powders are prone to blocking the furnace during aerosolization and powder making, and have low hardness, making it difficult to meet the needs of additive manufacturing for high hardness and wear resistance.
By adjusting the insulation crucible temperature and atomization pressure during argon atomization process, the fluidity and atomization stability of the alloy liquid are ensured, and W elements are added to promote the formation of BCC phase and the formation of W-rich second phase dendrites , improve the hardness and wear resistance of the alloy.
It significantly improves the hardness and wear resistance of high-entropy alloy powder, ensures the stability and efficiency of the aerosol powder making process, and is suitable for additive manufacturing such as laser cladding and 3D printing.
Smart Images

Figure CN119387579A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas atomization powder making, and in particular to a preparation method and application of a wear-resistant eutectic high entropy alloy powder with excellent performance, which can improve the stability of the powder gas atomization process and improve the physical properties of the powder. Background Art
[0002] High entropy alloy is a new type of alloy system that has emerged in recent years. Its design concept is different from that of traditional alloys and it has many novel properties. High entropy alloys are generally composed of four or more elements, with the atomic percentage of each element ranging from 5% to 35%, and the alloy structure formed is usually FCC or BCC structure. Eutectic alloy is an alloy with two-phase alternating distribution structure generated by liquid metal crystallizing into two solid phases at a constant temperature. Eutectic high entropy alloy has the characteristics of high strength, high hardness, good corrosion resistance and wear resistance, and excellent high temperature stability.
[0003] With the development of new technologies such as injection molding, 3D printing, thermal spraying, laser cladding, and hot isostatic pressing, higher requirements are placed on the performance of metal powders used in additive manufacturing. Compared with other powder making technologies, metal alloy powders prepared by gas atomization powder making have the characteristics of uniform composition and organization, high fine powder yield, good fluidity, good bulk density, high sphericity, controllable particle size, and low impurity element content. They are widely used in aerospace, nuclear power, military industry, marine ships and other fields. At present, gas atomization powder making has become one of the main methods for producing high-performance metal and alloy powders.
[0004] At present, CoCrFeNi is a typical high entropy alloy with FCC phase structure and good plasticity and toughness. After adding Al element, its structure will be transformed into BCC phase, thus improving its hardness, but the hardness (300-400HV 0.3 ) Compared with conventional high entropy alloy wear-resistant alloy (500-700HV 0.3 ) is lower.
[0005] In addition, the more components a high entropy alloy has, the higher its viscosity will be; and the viscosity of the high entropy alloy liquid during atomization has an important influence on the success of atomization and the atomization effect (the properties of the produced powder). Generally, the preparation of multi-component high entropy alloy powders is prone to furnace blockage and the physical properties of the prepared powder are poor. Summary of the invention
[0006] The problem to be solved by the present invention is to provide a wear-resistant eutectic high entropy alloy powder for additive manufacturing, which significantly improves the hardness of the high entropy alloy and has good wear resistance. At the same time, the present invention also provides a method for preparing the wear-resistant eutectic high entropy alloy powder, which timely adjusts the temperature and atomization pressure of the heat-insulating crucible during the argon atomization process to ensure that the furnace is not blocked and the atomization process is stable, thereby improving the physical properties of the powder. In addition, the present invention also provides an application of the wear-resistant eutectic high entropy alloy powder.
[0007] The present invention discloses a wear-resistant eutectic high-entropy alloy powder for additive manufacturing, wherein the chemical components of the powder include Al, Co, Cr, Fe, Ni and W.
[0008] The invention discloses a wear-resistant eutectic high entropy alloy powder for additive manufacturing, wherein the atomic percentage of the chemical composition is: Al: 16.5-20.5%, Co: 28.0-31.5%, Cr: 9.0-11.0%, Fe: 8.5-10.5%, Ni: 29.0-31.5%, W: 1.8-2.4%, the sum of Cr and Al is 26.0-30.5%, the sum of Al and W is 18.5-22.8%, and the remainder is inevitable impurities; the contents of C, S and P in the impurity elements are all less than 150ppm, and the contents of O and N are all less than 100ppm.
[0009] The present invention discloses a wear-resistant eutectic high entropy alloy powder for additive manufacturing, and the atomic percentage of the chemical composition is preferably: Al: 17%, Co: 31.1%, Cr: 9.5%, Fe: 9.5%, Ni: 31%, W: 1.9%, and the remainder is inevitable impurities; the contents of C, S, and P in the impurity elements are 55ppm, 12ppm, and 32ppm respectively, the content of O is 87ppm, and the content of N is 44ppm.
[0010] The present invention discloses a wear-resistant eutectic high entropy alloy powder for additive manufacturing, and the atomic percentage of the chemical composition is preferably: Al: 18.5%, Co: 30.0%, Cr: 11.0%, Fe: 10.5%, Ni: 30.0%, W: 2.0%, and the balance is inevitable impurities; the contents of C, S, and P in the impurity elements are 58ppm, 19ppm, and 29ppm respectively, the content of O is 94ppm, and the content of N is 49ppm.
[0011] The present invention discloses a wear-resistant eutectic high entropy alloy powder for additive manufacturing, and the atomic percentage of its chemical composition is preferably: Al: 20.5%, Co: 28.0%, Cr: 9.5%, Fe: 10.0%, Ni: 29.7%, W: 2.3%, and the remainder is inevitable impurities; the contents of C, S, and P in the impurity elements are 44ppm, 9ppm, and 16ppm respectively, the content of O is 92ppm, and the content of N is 56ppm.
[0012] The wear-resistant eutectic high entropy alloy powder for additive manufacturing of the present invention has a particle size range of 22-45 μm, 15-53 μm, 45-105 μm, 53-150 μm, and 75-150 μm, and a fluidity of 13.5-16 s / 50 g.
[0013] The wear-resistant eutectic high entropy alloy powder for additive manufacturing of the present invention has a sphericity of 95-100%.
[0014] The advantages of the wear-resistant eutectic high entropy alloy powder component of the present invention are: first, W is a relatively typical high melting point metal with high strength, high hardness and good wear resistance; based on the BCC type high entropy alloy AlCoCrFeNi, W element is added to promote the formation of BBC phase, and a second phase dendrite rich in W is formed at the grain boundary, so that the hardness of the AlCoCrFeNi series high entropy alloy is significantly improved, and it has good wear resistance; second, 9.0-11.0% Cr element and 16.5-20.5% Al element are added to improve the corrosion resistance of the cladding layer: when the AlCoCrFeNiW high entropy alloy is molten, the corrosion resistance of the cladding layer is improved; When the atomic ratio of Cr in the coating exceeds 9.0% and the atomic ratio of Al exceeds 14.6%, a dense Cr2O3 and Al2O3 passivation film will be formed on the surface of the cladding layer to improve the corrosion resistance of the cladding layer. However, when the Cr content gradually increases, the hardness of the cladding layer will gradually decrease. Therefore, in order to ensure that the high-entropy alloy cladding layer has high hardness and certain corrosion resistance, the sum of the atomic ratios of Cr and Al should be 26.0-30.5%. Third, adding 1.6-2.4% W and 16.5-20.5% Al can significantly improve the hardness of the cladding layer: Co, Cr, Fe, and Ni elements combine to easily form a single face-centered cubic (FCC) solid solution. Adding Al to the CoCrFeNi high entropy alloy can gradually transform the alloy structure from FCC phase to BCC phase, thereby improving the hardness of the alloy. The W atomic radius is significantly larger than that of Co, Cr, Fe, and Ni atoms, and is close to that of Al atoms. Therefore, the addition of W has a similar effect to that of Al, and both can promote the formation of BCC phase. After adding W, W-rich second phase dendrites will be formed in the cladding layer, which significantly improves the hardness of the cladding layer. However, unlike Al, due to the W element The melting point is very high, and it is easy to form some unmelted W-rich fine second phase distributed on the substrate. Adding too much W element during laser cladding will form unmelted W particles in the cladding layer, resulting in an increase in large holes in the cladding layer after adding W element; therefore, in order to ensure that the high entropy alloy cladding layer has a higher hardness while reducing the defects in the cladding layer, it is necessary to ensure that the sum of the atomic ratios of Al and W elements should be between 18.5 and 22.8%; Fourth, the alloy powder has a low impurity content and high purity, which is conducive to ensuring the uniform composition and organization of the laser cladding sample, ensuring the consistent surface quality of the cladding layer, and promoting the uniform hardness of the cladding layer.
[0015] The present invention provides a method for preparing wear-resistant eutectic high entropy alloy powder for additive manufacturing, comprising the following steps:
[0016] ① Polishing and cleaning of raw materials: polish aluminum beans, electrolytic cobalt plates, metal chromium blocks, pure iron rods, nickel plates and tungsten bars with 600-grit sandpaper until the surface is bright, then wipe the surface of the raw materials with a clean dust-free cloth dipped in alcohol, and place them in a cool place to air dry for later use;
[0017] ② Batching and charging: 100kg of materials are batched according to the atomic percentage of alloy elements, among which Al, Co, Cr, Fe, Ni, and W elements are all added with high-purity single metals; when adding materials, tungsten bars are placed at the bottom of the melting crucible (alumina crucible), nickel plates and electrolytic cobalt plates are arranged vertically and evenly close to the crucible wall, pure iron rods are placed vertically in the middle and lower part of the crucible, metal chromium blocks are evenly sprinkled in the middle and upper part of the crucible, and aluminum beans are added twice; the bottom of the materials is tightly charged, and the middle and upper parts are loose;
[0018] ③ Vacuuming and gas replacement: Turn on the mechanical vacuum pump and Roots vacuum pump in sequence. When the vacuum degree is less than 30Pa, turn off the vacuum pump and open the argon gas filling valve. When the furnace pressure in the melting chamber reaches 5×10 4 Pa, stop charging to complete the first gas replacement, turn on the power of the melting crucible and the insulation crucible, start preheating the melting crucible at a power of 25kw, and start preheating the insulation crucible at a power of 12.5kw; during the preheating process, perform replacement again according to the above vacuuming and gas replacement steps, repeat the replacement steps 1-3 times, and the furnace pressure of the melting chamber is 1×10 5 Pa;
[0019] ④Argon protection smelting: The power of the smelting crucible is gradually increased at 20kw / 20min. The smelting crucible is tilted 2-3 times during the alloy melting process. When the raw materials are completely melted into molten liquid, the power of the smelting crucible is maintained at about 110kw. Refining is carried out at the refining temperature for 8-10 minutes. At the same time, the crucible is tilted 2-3 times to homogenize the molten liquid. When the smelting end point, i.e. 10-15 minutes before the start of atomization, aluminum beans are added through the secondary feeding device;
[0020] ⑤ Argon atomization: When the alloy liquid temperature reaches the furnace discharge temperature and the insulation crucible temperature reaches the insulation temperature, open the atomizing gas pressure regulating valve and quickly adjust it to the set pressure; at the same time, start pouring the alloy liquid into the insulation crucible, and the molten liquid flows out from the insulation crucible through the guide nozzle at the bottom of the atomizing spray plate at the bottom of the insulation crucible, and is broken, atomized, and solidified into metal powder by argon gas; in this process, when about 80% of the alloy liquid remains in the melting crucible, increase the insulation crucible temperature and reduce the atomization pressure at the same time; when about 60-70% of the alloy liquid remains in the melting crucible, the insulation crucible is increased by 40-50℃, and the atomization pressure is reduced by 0.4-0.7Mpa;
[0021] ⑥ Airflow classifier screening: After the powder is cooled and collected, the airflow classification frequency is adjusted to 6.5Hz for feeding frequency, 18.5-20.5Hz for primary frequency, and 12.1-14.4Hz for secondary frequency. The airflow classifier is used to screen out powders with secondary discharge ports of 22-45μm and 15-53μm;
[0022] ⑦ Vibrating screen screening: adjust the energy of the ultrasonic controller of the ultrasonic vibrating screen to 60%, select 100 mesh and 270 mesh, 150 mesh and 325 mesh, 100 mesh and 200 mesh screens; pour the coarse powder in the first-level feeding port into the vibrating screen feeding port for screening, the feeding speed is 40g / s, and then obtain 45-105μm, 53-150μm, 75-150μm powders.
[0023] In step ④, the refining temperature of the high entropy alloy is 1550-1560°C; in step ⑤, the furnace temperature of the high entropy alloy is 1640-1650°C.
[0024] In step ⑤, the holding temperature of the holding crucible is 1330-1340°C; when the melting crucible is 80% liquid, the power is gradually increased, and when the melting crucible is 60% liquid, the temperature of the holding crucible is increased to 1380-1390°C.
[0025] In steps ③, ④ and ⑤, the argon gas is high-purity argon gas with a purity greater than 99.9995%.
[0026] In step ⑤: the argon pressure used for initial atomization is 2.4-2.5 MPa. When the melting crucible is 80% liquid, the pressure is gradually reduced. When the melting crucible is 60% liquid, the atomization pressure is adjusted to 1.8-2.0 MPa.
[0027] In step ⑤: the spray disc used for atomization is of an annular gap type, the guide nozzle is a tightly coupled gas atomization nozzle, and the diameter of the guide nozzle is 5.0-6.0 mm.
[0028] The advantages of the preparation method of the present invention are: 1. During the argon atomization process, when 80% of the alloy liquid in the melting crucible remains, the temperature of the heat-insulating crucible is increased to reduce the viscosity of the alloy liquid flow (the viscosity of the metal melt generally decreases with the increase of temperature): 1. Improving the stability of the atomization process: improving the fluidity of the alloy liquid, promoting the alloy liquid to pass through the guide nozzle, and promoting the smooth and continuous atomization process; 2. Improving the sphericity and surface quality of the powder: reducing the surface tension of the metal liquid, the metal droplets contain more heat, and the powder solidification process takes a long time (keeping the liquid The longer the liquid metal droplets remain in the liquid state, the easier it is to spheroidize (the longer the spheroidization time), which improves the powder sphericity and powder surface quality, and reduces powder surface defects; 3. Narrow particle size distribution: As the metal droplets remain in the liquid state for an increasing period of time, the metal melt is conducive to being fully broken by argon gas to form fine droplets, thereby increasing the fine powder recovery rate and narrowing the particle size distribution; 2. During the argon atomization process, when 80% of the alloy liquid remains in the melting crucible, reducing the atomization pressure is conducive to increasing the negative pressure value in the atomization gas flow field and improving the suction effect on the metal melt. It is conducive to the alloy liquid to pass through the guide nozzle smoothly and continuously in the later stage of atomization, and improve the stability and continuity of atomization; 3. In the argon protection smelting process, aluminum beans are added through the secondary feeding device 10-15 minutes before the end of smelting, that is, 1. Reduce the oxidation and burning of Al elements to prevent the deviation of powder composition; 2. 10-15min aluminum beans have sufficient time to completely integrate into the alloy liquid to prevent the segregation (uneven) of powder composition; if aluminum beans are added more than 15min before the end of smelting, more Al elements will be burned and the composition will deviate; 3. Aluminum beans are used to reduce the oxygen content in the alloy liquid, thereby reducing the oxygen content of the powder and improving the purity of the powder; 4. The refining temperature and the furnace temperature (corresponding to the temperature at the end of smelting) are appropriate: too high refining temperature will cause burning of Cr elements, and too high furnace temperature will cause burning of Cr, Al and other elements (Al is a secondary feed, so only the furnace temperature will affect Al), thus causing powder composition deviation. Appropriate refining temperature and furnace temperature are conducive to the homogenization of powder composition and accurate composition.
[0029] The invention discloses an application of wear-resistant eutectic high entropy alloy powder in additive manufacturing. The high entropy alloy powder is used as cladding powder to perform laser cladding on the surface of the substrate material to obtain a cladding layer. The cladding layer has high hardness and good wear resistance: the hardness of the cladding layer at room temperature is not less than 500HV 0.3 The laser cladding process parameters are: spot diameter 5mm, laser power 2.8-3.2kW, scanning rate 1000-1400mm / min, powder feeding amount 38-45g / min, overlap rate 50-60%.
[0030] The wear-resistant eutectic high entropy alloy powder of the present invention is used in additive manufacturing. The high entropy alloy powder is used as 3D printing powder, which is fed through a feeding system and scanned on a metal substrate to form a workpiece. After all scanning is completed and cooling, wire cutting is used to separate the workpiece from the metal substrate to obtain a typical block sample.
[0031] In summary, the wear-resistant eutectic high entropy alloy powder of the present invention has low impurity content, high purity, high hardness, good wear resistance and good corrosion resistance: the preparation method of the present invention ensures that the furnace is not blocked during the atomization of the multi-component high entropy alloy powder and the atomization process is stable, and the powder has good performance: narrow particle size distribution, high bulk density, high sphericity and good fluidity. Therefore, the present invention can be widely used in additive manufacturing of parts in the fields of aerospace, nuclear power and military industry through laser cladding, 3D printing, etc. to solve the problem of insufficient surface hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the surface morphology of the powder under a scanning electron microscope (magnified 200 times)
[0033] Figure 2 This is the surface morphology of the powder under a scanning electron microscope (magnified 1500 times) DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with the composition and specific preparation method of the wear-resistant eutectic high entropy alloy powder for additive manufacturing.
[0035] Example 1
[0036] A wear-resistant eutectic high entropy alloy powder for additive manufacturing, the atomic percentage of the chemical composition of which is: Al: 17%, Co: 31.1%, Cr: 9.5%, Fe: 9.5%, Ni: 31%, W: 1.9%, and the balance is inevitable impurities; the contents of C, S, and P in the impurity elements are 55ppm, 12ppm, and 32ppm respectively, the content of O is 87ppm, and the content of N is 44ppm.
[0037] The method for preparing the high entropy alloy powder comprises the following steps:
[0038] ① Polishing and cleaning of raw materials: polish aluminum beans, electrolytic cobalt plates, metal chromium blocks, pure iron rods, nickel plates and tungsten bars with 600-grit sandpaper until the surface is bright, then wipe the surface of the raw materials with a clean dust-free cloth dipped in alcohol, and place them in a cool place to air dry for later use;
[0039] ② Batching and charging: Batching is carried out according to the atomic percentage of alloy elements, with a total weight of 100kg; when charging, tungsten bars are placed at the bottom of the smelting crucible, nickel plates and electrolytic cobalt plates are arranged vertically and evenly close to the crucible wall, pure iron rods are placed vertically in the middle and lower part of the crucible, metal chromium blocks are evenly scattered in the middle and upper part of the crucible, and aluminum beans are charged twice; the bottom of the charging is tight and the middle and upper part is loose;
[0040] ③ Vacuuming and gas replacement: Turn on the mechanical vacuum pump and Roots vacuum pump in sequence. When the vacuum degree is less than 30Pa, turn off the vacuum pump and open the argon gas filling valve. When the furnace pressure in the melting chamber reaches 5×10 4 Pa, stop charging to complete the first gas replacement, turn on the power of the melting crucible and the insulation crucible, start preheating the melting crucible at a power of 25kw, and start preheating the tundish at a power of 12.5kw; during the preheating process, perform replacement again according to the above vacuuming and gas replacement steps, repeat the replacement steps 1-3 times, and the furnace pressure of the melting chamber is 1×10 5 Pa;
[0041] ④Argon protection smelting: The power of the smelting crucible is gradually increased at 20kw / 20min. The smelting crucible is tilted 2-3 times during the alloy melting process. When the raw materials are completely melted into molten liquid, the power of the smelting crucible is maintained at about 110kw. Refining is carried out at 1550℃ for 8 minutes. At the same time, the crucible is tilted 2-3 times to homogenize the molten liquid. When the smelting end point, that is, 10 minutes before the start of atomization, aluminum beans are added through the secondary feeding device;
[0042] ⑤ Argon atomization: When the alloy liquid temperature reaches 1640℃ and the temperature of the insulation crucible reaches 1330℃, open the atomizing gas pressure regulating valve and quickly adjust the atomizing pressure to 2.4MPa; at the same time, start pouring the alloy liquid into the insulation crucible, and the molten liquid flows out from the insulation crucible through the 6.0mm guide nozzle at the bottom of the atomizing spray plate at the bottom of the insulation crucible, and is broken, atomized, and solidified into metal powder by argon gas; in this process, when about 80% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible and reduce the atomizing pressure at the same time; when about 70% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible by 50℃ and reduce the atomizing pressure to 1.8Mpa at the same time;
[0043] (6) Airflow classifier screening: After the powder is cooled and collected, the airflow classification frequency is adjusted to 6.5 Hz for the feed frequency, 20.5 Hz for the primary frequency, and 14.4 Hz for the secondary frequency. The airflow classifier is used to screen out the powder with a size of 15-45 μm at the secondary discharge port;
[0044] (7) Ultrasonic vibration sieve screening: adjust the energy of the ultrasonic controller of the ultrasonic vibration sieve to 60%, select 150 mesh and 325 mesh screens, pour the coarse powder in the first-level discharge port into the discharge port of the vibration sieve for screening, and the discharge speed is 40 g / s.
[0045] from Figure 1 , Figure 2 It can be seen that the high entropy alloy powder prepared by the materials and methods of this embodiment has good surface morphology, high sphericity, uniform particle size, and a small proportion of hollow powder and satellite powder.
[0046] The high entropy alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were: spot diameter 5 mm, laser power 3.0 kW, scanning rate 1000 mm / min, powder feeding amount 42 g / min, overlap rate 50%, and a laser cladding layer was obtained.
[0047] Example 2
[0048] A wear-resistant eutectic high entropy alloy powder for additive manufacturing, the atomic percentage of the chemical composition of which is: Al: 18.5%, Co: 30.0%, Cr: 11.0%, Fe: 10.5%, Ni: 30.0%, W: 2.0%, and the balance is inevitable impurities; the contents of C, S, and P in the impurity elements are 58ppm, 19ppm, and 29ppm respectively, the content of O is 94ppm, and the content of N is 49ppm.
[0049] The method for preparing the high entropy alloy powder comprises the following steps:
[0050] ① Polishing and cleaning of raw materials: polish aluminum beans, electrolytic cobalt plates, metal chromium blocks, pure iron rods, nickel plates and tungsten bars with 600-grit sandpaper until the surface is bright, then wipe the surface of the raw materials with a clean dust-free cloth dipped in alcohol, and place them in a cool place to air dry for later use;
[0051] ② Batching and charging: Batching is carried out according to the atomic percentage of alloy elements, with a total weight of 100kg; when charging, tungsten bars are placed at the bottom of the alumina crucible, nickel plates and electrolytic cobalt plates are arranged vertically and evenly close to the crucible wall, pure iron rods are placed vertically in the middle and lower part of the crucible, metal chromium blocks are evenly sprinkled in the middle and upper part of the crucible, and aluminum beans are charged twice; the bottom of the charging is tight and the middle and upper part is loose;
[0052] ③ Vacuuming and gas replacement: Turn on the mechanical vacuum pump and Roots vacuum pump in sequence. When the vacuum degree is less than 30Pa, turn off the vacuum pump and open the argon gas filling valve. When the furnace pressure in the melting chamber reaches 5×10 4 Pa, stop charging to complete the first gas replacement, turn on the power of the melting crucible and the insulation crucible, start preheating the melting crucible at a power of 25kw, and start preheating the insulation crucible at a power of 12.5kw; during the preheating process, perform replacement again according to the above vacuuming and gas replacement steps, repeat the replacement steps 1-3 times, and the furnace pressure of the melting chamber is 1×10 5 Pa;
[0053] ④Argon protection smelting: The power of the smelting crucible is gradually increased at 20kw / 20min. The smelting crucible is tilted 2-3 times during the alloy melting process. When the raw materials are completely melted into molten liquid, the power of the smelting crucible is maintained at about 110kw. Refining is carried out at 1555℃ for 9 minutes. At the same time, the crucible is tilted 2-3 times to homogenize the molten liquid. When the smelting end point, i.e. 12 minutes before the start of atomization, aluminum beans are added through the secondary feeding device;
[0054] ⑤ Argon atomization: When the alloy liquid temperature reaches 1645℃ and the temperature of the insulation crucible reaches 1335℃, open the atomizing gas pressure regulating valve and quickly adjust the atomizing pressure to 2.45MPa; at the same time, start pouring the alloy liquid into the insulation crucible, and the molten liquid flows out from the insulation crucible through the 5.5mm guide nozzle at the bottom of the atomizing spray plate at the bottom of the insulation crucible, and is broken, atomized, and solidified into metal powder by argon gas; in this process, when about 80% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible and reduce the atomizing pressure at the same time; when about 65% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible by 45℃ and reduce the atomizing pressure to 1.9Mpa;
[0055] ⑥ Airflow classifier screening: After the powder is cooled and collected, the airflow classification frequency is adjusted to 6.5Hz for feeding frequency, 20.0Hz for primary frequency and 13.6Hz for secondary frequency. The airflow classifier is used to screen out the powder with a size of 22-45μm at the secondary discharge port;
[0056] ⑦ Ultrasonic vibration screen screening: Adjust the energy of the ultrasonic controller of the ultrasonic vibration screen to 60%, and select 150 mesh and 325 mesh screens. Pour the coarse powder from the first-level discharge port into the discharge port of the vibration screen for screening, and the discharge speed is 40g / s.
[0057] The high entropy alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were as follows: spot diameter 5 mm, laser power 3.2 kW, scanning rate 1300 mm / min, powder feeding amount 45 g / min, overlap rate 55%, and a laser cladding layer was obtained.
[0058] Example 3
[0059] A wear-resistant eutectic high entropy alloy powder for additive manufacturing, the atomic percentage of the chemical composition of which is: Al: 20.5%, Co: 28.0%, Cr: 9.5%, Fe: 10.0%, Ni: 29.7%, W: 2.3%, and the balance is inevitable impurities; the contents of C, S, and P in the impurity elements are 44ppm, 9ppm, and 16ppm respectively, the content of O is 92ppm, and the content of N is 56ppm.
[0060] The method for preparing the high entropy alloy powder comprises the following steps:
[0061] ① Polishing and cleaning of raw materials: polish aluminum beans, electrolytic cobalt plates, metal chromium blocks, pure iron rods, nickel plates and tungsten bars with 600-grit sandpaper until the surface is bright, then wipe the surface of the raw materials with a clean dust-free cloth dipped in alcohol, and place them in a cool place to air dry for later use;
[0062] ② Batching and charging: Batching is carried out according to the atomic percentage of alloy elements, with a total weight of 100kg; when charging, tungsten bars are placed at the bottom of the alumina crucible, nickel plates and electrolytic cobalt plates are arranged vertically and evenly close to the crucible wall, pure iron rods are placed vertically in the middle and lower part of the crucible, metal chromium blocks are evenly sprinkled in the middle and upper part of the crucible, and aluminum beans are charged twice; the bottom of the charging is tight and the middle and upper part is loose;
[0063] ③ Vacuuming and gas replacement: Turn on the mechanical vacuum pump and Roots vacuum pump in sequence. When the vacuum degree is less than 30Pa, turn off the vacuum pump and open the argon filling valve. When the furnace pressure in the melting chamber reaches 5×10 4 Pa, stop charging to complete the first gas replacement, turn on the power of the melting crucible and the insulation crucible, start preheating the melting crucible at a power of 25kw, and start preheating the insulation crucible at a power of 12.5kw; during the preheating process, perform replacement again according to the above vacuuming and gas replacement steps, repeat the replacement steps 1-3 times, and the furnace pressure of the melting chamber is 1×10 5 Pa;
[0064] ④Argon protection smelting: The power of the smelting crucible is gradually increased at 20kw / 20min. The smelting crucible is tilted 2-3 times during the alloy melting process. When the raw materials are completely melted into molten liquid, the power of the smelting crucible is maintained at about 110kw. Refining is carried out at 1560℃ for 10 minutes. At the same time, the crucible is tilted 2-3 times to homogenize the molten liquid. When the smelting end point, that is, 15 minutes before the start of atomization, aluminum beans are added through the secondary feeding device;
[0065] ⑤ Argon atomization: When the alloy liquid temperature reaches 1650℃ and the temperature of the insulation crucible reaches 1340℃, open the atomizing gas pressure regulating valve and quickly adjust the atomizing pressure to 2.5MPa; at the same time, start pouring the alloy liquid into the insulation crucible, and the molten liquid flows out from the insulation crucible through the 5.0mm guide nozzle at the bottom of the atomizing spray plate at the bottom of the insulation crucible, and is broken, atomized, and solidified into metal powder by argon gas; in this process, when about 80% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible and reduce the atomizing pressure at the same time; when about 60% of the alloy liquid remains in the melting crucible, increase the temperature of the insulation crucible by 40℃ and reduce the atomizing pressure to 2.0Mpa at the same time;
[0066] ⑥ Airflow classifier screening: After the powder is cooled and collected, the airflow classification frequency is adjusted to 6.5Hz for feeding frequency, 18.5Hz for primary frequency and 12.6Hz for secondary frequency. The airflow classifier is used to screen out the powder with a size of 15-53μm at the secondary discharge port;
[0067] ⑦ Ultrasonic vibration screen screening: adjust the energy of the ultrasonic controller of the ultrasonic vibration screen to 60%, select 100 mesh and 200 mesh screens, pour the coarse powder in the first-level discharge port into the discharge port of the vibration screen for screening, and the discharge speed is 40g / s.
[0068] The high entropy alloy powder obtained in this embodiment was laser clad in two layers on a 100*100 mm 316L test block. The laser cladding process parameters were as follows: spot diameter 5 mm, laser power 3.0 kW, scanning rate 1100 mm / min, powder feeding amount 40 g / min, overlap rate 60%, and a laser cladding layer was obtained.
[0069] The high entropy alloy powder obtained by the preparation method of the present invention has good fluidity, high bulk density, small powder span, narrow particle size distribution, and the powder measured laser diffraction particle size is basically consistent with the nominal particle size; and the cladding layer prepared by the powder and laser cladding process of the present invention has high hardness and good wear resistance. Therefore, it can be widely used in additive manufacturing, and specific examples are as follows:
[0070] The physical properties of the high entropy alloy powders obtained in Examples 1-3 of the present invention were tested as follows using the following experimental instruments: 1. Powder composition: an X-ray fluorescence spectrometer was used to detect the main elements, an oxygen and nitrogen analyzer was used to detect O and N, a carbon and sulfur analyzer was used to detect C and S, and ICP-OES was used to detect trace and trace elements; 2. Powder particle size: a laser particle size analyzer was used to measure the particle size distribution of the high entropy alloy powder; 3. Powder fluidity: a Hall flowmeter was used to measure the flow rate of the high entropy alloy powder; 4. Powder bulk density: a powder comprehensive property tester was used to measure the bulk density of the high entropy alloy powder; 5. Coating hardness: a micro Vickers hardness tester was used to measure the hardness of the cladding layer, and five points were detected at equal distances to take the average.
[0071] Among them, the coarse particles of high entropy alloy powder obtained in Examples 1-3 can be used in laser cladding, and the physical properties and mechanical properties of the powder are shown in Table 1.
[0072] Table 1 Physical properties and mechanical properties of powders for laser cladding
[0073]
[0074] As can be seen from Table 1, the alloy powder of the present invention has a narrow particle size distribution, high bulk density, and high sphericity, which is beneficial to reducing powder splashing during laser cladding, improving the surface flatness and density of the cladding layer, and thus improving the surface hardness of the cladding layer. In addition, the alloy powder of the present invention has good fluidity, which is beneficial to the stability and continuity of the laser cladding powder feeding process. In addition, the alloy powder of the present invention has a low impurity content and high purity, which is beneficial to ensuring the uniform composition and organization of the laser cladding sample, ensuring the consistent surface quality of the cladding layer, and promoting the uniform surface hardness of the cladding layer.
[0075] Among them, the fine particles of high entropy alloy powder obtained in Examples 1-3 can be used in 3D printing and thermal spraying. The test results of the physical properties of the powder are shown in Table 2
[0076] Table 1 Physical properties of powders for 3D printing and thermal spraying
[0077]
[0078] It can be seen from Table 2 that the high entropy alloy powder for 3D printing and spraying prepared by the present invention has good fluidity, high bulk density, small powder span, narrow particle size distribution, the actual laser diffraction particle size of the powder is basically consistent with the nominal particle size, and the powder has good physical properties.
Claims
1. A wear-resistant eutectic high entropy alloy powder for additive manufacturing, characterized by: The chemical composition includes Al, Co, Cr, Fe, Ni, and W.
2. The wear-resistant eutectic high entropy alloy powder according to claim 1, characterized in that: The atomic percentages of its chemical composition are: Al: 16.5-20.5%, Co: 28.0-31.5%, Cr: 9.0-11.0%, Fe: 8.5-10.5%, Ni: 29.0-31.5%, W: 1.8-2.4%, and the sum of Cr and Al is 26.0-30.5%, the sum of Al and W is 18.5-22.8%, and the remainder is unavoidable impurities; the contents of C, S and P in the impurity elements do not exceed 150ppm, and the contents of O and N do not exceed 100ppm.
3. The wear-resistant eutectic high entropy alloy powder according to claim 2, characterized in that: The atomic percentage of its chemical composition is preferably: Al: 17%, Co: 31.1%, Cr: 9.5%, Fe: 9.5%, Ni: 31%, W: 1.9%, and the remainder is inevitable impurities; the contents of C, S, and P elements in the impurity elements are 55ppm, 12ppm, and 32ppm respectively, the content of O element is 87ppm, and the content of N element is 44ppm.
4. The wear-resistant eutectic high entropy alloy powder according to claim 2, characterized in that: The atomic percentage of its chemical composition is preferably: Al: 18.5%, Co: 30.0%, Cr: 11.0%, Fe: 10.5%, Ni: 30.0%, W: 2.0%, and the remainder is inevitable impurities; the contents of C, S, and P elements in the impurity elements are 58ppm, 19ppm, and 29ppm respectively, the content of O element is 94ppm, and the content of N element is 49ppm.
5. The wear-resistant eutectic high entropy alloy powder according to claim 2, characterized in that: The atomic percentage of its chemical composition is preferably: Al: 20.5%, Co: 28.0%, Cr: 9.5%, Fe: 10.0%, Ni: 29.7%, W: 2.3%, and the remainder is inevitable impurities; the contents of C, S, and P elements in the impurity elements are 44ppm, 9ppm, and 16ppm respectively, the content of O element is 92ppm, and the content of N element is 56ppm.
6. The wear-resistant eutectic high entropy alloy powder according to claim 2, characterized in that: The particle size ranges of the powder are: 22-45μm, 15-53μm, 45-105μm, 53-150μm, 75-150μm, the fluidity is 13.5-16s / 50g; the sphericity is 95-100%.
7. A method for preparing wear-resistant eutectic high entropy alloy powder for additive manufacturing, comprising the following steps: ① Polishing and cleaning of raw materials: polish aluminum beans, electrolytic cobalt plates, metal chromium blocks, pure iron rods, nickel plates and tungsten bars with 600-grit sandpaper until the surface is bright, then wipe the surface of the raw materials with a clean dust-free cloth dipped in alcohol, and place them in a cool place to air dry for later use; ② Batching and charging: 100kg of materials are batched according to the atomic percentage of alloy elements, among which Al, Co, Cr, Fe, Ni, and W elements are all added with high-purity single metals; when adding materials, tungsten bars are placed at the bottom of the melting crucible (alumina crucible), nickel plates and electrolytic cobalt plates are arranged vertically and evenly close to the crucible wall, pure iron rods are placed vertically in the middle and lower part of the crucible, metal chromium blocks are evenly sprinkled in the middle and upper part of the crucible, and aluminum beans are added twice; the bottom of the materials is tightly charged, and the middle and upper parts are loose; ③ Vacuuming and gas replacement: Turn on the mechanical vacuum pump and Roots vacuum pump in sequence. When the vacuum degree is less than 30Pa, turn off the vacuum pump and open the argon gas filling valve. When the furnace pressure in the melting chamber reaches 5×10 4 Pa, stop charging to complete the first gas replacement, turn on the power of the melting crucible and the insulation crucible, start preheating the melting crucible at a power of 25kw, and start preheating the insulation crucible at a power of 12.5kw; during the preheating process, perform replacement again according to the above vacuuming and gas replacement steps, repeat the replacement steps 1-3 times, and the furnace pressure of the melting chamber is 1×10 5 Pa; ④Argon protection smelting: The power of the smelting crucible is gradually increased at 20kw / 20min. The smelting crucible is tilted 2-3 times during the alloy melting process. When the raw materials are completely melted into molten liquid, the power of the smelting crucible is maintained at about 110kw. Refining is carried out at the refining temperature for 8-10 minutes. At the same time, the crucible is tilted 2-3 times to homogenize the molten liquid. When the smelting end point, i.e. 10-15 minutes before the start of atomization, aluminum beans are added through the secondary feeding device; ⑤ Argon atomization: When the alloy liquid temperature reaches the furnace discharge temperature and the insulation crucible temperature reaches the insulation temperature, open the atomizing gas pressure regulating valve and quickly adjust it to the set pressure; at the same time, start pouring the alloy liquid into the insulation crucible, and the molten liquid flows out from the insulation crucible through the guide nozzle at the bottom of the atomizing spray plate at the bottom of the insulation crucible, and is broken, atomized, and solidified into metal powder by argon gas; in this process, when about 80% of the alloy liquid remains in the melting crucible, increase the insulation crucible temperature and reduce the atomization pressure at the same time; when about 60-70% of the alloy liquid remains in the melting crucible, the insulation crucible is increased by 40-50℃, and the atomization pressure is reduced by 0.4-0.7Mpa; ⑥ Airflow classifier screening: After the powder is cooled and collected, the airflow classification frequency is adjusted to 6.5Hz for feeding frequency, 18.5-20.5Hz for primary frequency, and 12.1-14.4Hz for secondary frequency. The airflow classifier is used to screen out powders with secondary discharge ports of 22-45μm and 15-53μm; ⑦ Vibrating screen screening: adjust the energy of the ultrasonic controller of the ultrasonic vibrating screen to 60%, select 100 mesh and 270 mesh, 150 mesh and 325 mesh, 100 mesh and 200 mesh screens; pour the coarse powder in the first-level feeding port into the vibrating screen feeding port for screening, the feeding speed is 40g / s, and then obtain 45-105μm, 53-150μm, 75-150μm powders.
8. The preparation method according to claim 7, characterized in that: In step ④, the refining temperature of the high entropy alloy is 1550-1560°C; in step ⑤, the furnace temperature of the high entropy alloy is 1640-1650°C.
9. The preparation method according to claim 7, characterized in that: In step ⑤: the insulation temperature of the insulation crucible is 1330-1340° C.; the power is gradually increased after the melting crucible reaches 80% of the liquid, and the temperature of the insulation crucible is increased to 1380-1390° C. when the melting crucible reaches 60% of the liquid; the initial atomizing argon pressure is 2.4-2.5 MPa, and the pressure is gradually reduced after the melting crucible reaches 80% of the liquid, and the atomizing pressure is adjusted to 1.8-2.0 MPa when the melting crucible reaches 60% of the liquid.
10. The application of the wear-resistant eutectic high entropy alloy powder in additive manufacturing is to use the high entropy alloy powder as cladding powder to perform laser cladding on the surface of the substrate material to obtain a cladding layer; the cladding layer has high hardness and good wear resistance: the hardness of the cladding layer at room temperature is not less than 500HV 0.3 .